Reservoir and Residence, Port of Spain Trinidad - (:unkn) unknown (My University, 2011)
The postcards shows a view of the Maraval Reservoir, located in the town of Maraval on the island of Trinidad in the Republic of Trinidad and Tobago.
Colour: Black and white; Style: Landscape; Other: Unbordered, Undivided
Keywords: Trinidad and Tobago; Postcards; Reservoirs--Trinidad and Tobago; Cities and towns--Trinidad and Tobago--Maraval; [1908]; Hedges--Trinidad and Tobago; Trees--Trinidad and Tobago; Architecture, Domestic--Trinidad and Tobago; Dwellings--Trinidad and Tobago; Wooden-frame houses--Trinidad and Tobago; Architecture--Trinidad and Tobago